L’impresa Ristori-Capranica. Invenzione e svuotamento della compagnia grandattoriale - Cavaglieri, Livia (Drammaturgia, 2024)
This essay offers an interpretation of the entrepreneurial dimension of Adelaide Ristori’s theater, focusing on the different ways in which the actress, and her husband, Giuliano Capranica marquis del Grillo, organised the theatrical company, along thirty-five years of activity. From the invention of the Grande Attore style company to its draining, this essay focuses on the general functioning of the ‘two-headed’ capocomicato that distinguished the Capranica-Ristori troupe and analyses the model of extractive touring, recognizing the relevant role played, on the strategic level, by Giuliano Capranica.